The Socio-Historical Criticism Toward Sunnah and Ijma' In Fazlur Rahman Perspective - Fauzi Muhammad; Adrianus Chatib; Fuad Rahman (INNOVATIO: Journal for Religious Innovation Studies, 2021)
Sunnah and Ijma' are among the two propositions of Islamic law used by all schools of Sunni, which by Fazlur Rahman as a neo-modernist gives both specific concepts, and he succeeded in answering orientalists’ criticisms regarding the existence and strengths. This study uses a qualitative approach with descriptive analysis, and includes library research type. The analysis technique used is descriptive technique. The results of this study show that Fazlur Rahman recognizes the Sunnah and Ijma’ as the postulates of Islamic law, and he also describes them based on social and historical conditions critically, and refutes all criticisms and doubts of the orientalists, with the arguments can be proven by facts, data, and spectacular. This shows that the Sunnah and Ijma’ in Fazlur Rahman's view are the same as the previous classical scholars, and he is even able to describe them in a socio-historical and historical-critical frame. Abstrak: Sunnah dan Ijma’ merupakan diantara dua dalil hukum Islam yang digunakan oleh semua mazhab Sunni, yang oleh Fazlur Rahman sebagai seorang neo-modernis memberikan konsep keduanya yang spesifik, dan ia berhasil menjawab kritikan-kritikan para orientalis mengenai eksistensi dan kekuatan keduanya. Penelitian ini menggunakan pendekatan kualitatif yang bersifat deskriptif analisis, dan termasuk jenis penelitian kepustakaan. Teknik analisis yang digunakan adalah Teknik deskriptif. Hasil penelitian ini menunjukkan bahwa Fazlur Rahman mengakui Sunnah dan Ijma sebagai dalil hukum Islam, dan ia juga memaparkan keduanya berdasarkan kondisi sosial dan historis secara kritis, serta membantah semua kritikan dan keraguan para orientalis, dengan argumen-argumen yang dapat dibuktikan dengan fakta, data, dan spektakuler. Hal ini menunjukkan bahwa Sunnah dan Ijma dalam pandangan Fazlur Rahman sama dengan para ulama klasik terdahulu, dan bahkan ia mampu menguraikan keduanya dalam bingkai sosio-historis dan kritik-historis. Kata-kata kunci: sunnah, ijma’, Fazlur Rahman